Investigation of the Application of Various Water Additive Ratios on Unconfined Compressive Strength of Cement-Stabilized Amorphous Peat at Different Natural Moisture Contents - Atikah, Rahmi; Siti Noor Linda, Taib; Fauzan, Sahdi (Hindawi Publishing, 2018)
Natural peat is considered incapable of supporting built structure due to its poor engineering properties. Chemical stabilization is one of the peat soil improvement methods which has been studied by many researchers. This study describes an investigation of water additive (W/A) ratio application on cement-stabilized peat strength. Peat soil at different moisture contents, which are 1210%, 803%, and 380%, were stabilized with cement by W/A ratio of 2.0, 2.5, 3.0, 3.5, and 4.0. Unconfined compressive strength (UCS) test was conducted after the specimens were being air-cured for 28 and 56 days. The result shows that there is an increase of UCS value as the decrease of W/A ratio (the increase of cement dosage) and the increase of curing time and peat moisture content. The higher strength found in the specimen with higher moisture content, compared to the lower one at the same W/A ratio, shows that the mix design of cement-stabilized peat using W/A ratio should have differed under different peat natural moisture contents. From the result, it is also found that cement hydrolysis reaction occurred despite the presence of humic acid in the peat soil, which by many studies is assumed will hinder the cement-soil reaction.